Generating urban structures. A method for urban planning supported by multi-agent systems and cellular automata. - Koenig, Reinhard (My University, 2011)
This work is based on the concept that the structure of a city can be defined by six basic urban patterns. To enable more complex urban planning as a long-term objective I have developed a simulation method for generating these basic patterns and for combining them to form various structures. The generative process starts with the two-dimensional organisation of streets followed by the parceling of the remaining areas. An agent-based diffusion-contact model is the basis of these first two steps. Then, with the help of cellular automata, the sites for building on are defined and a three-dimensional building structure is derived. I illustrate the proposed method by showing how it can be applied to generate possible structures for an urban area in the city of Munich.
Keywords: Stadtplanung; Stadtstruktur; Bebauung; Simulation; Methode; Cluster; Baustruktur; Vernetzung